Foodborne cereulide causes beta-cell dysfunction and apoptosis. - Roman Vangoitsenhoven; Dieter Rondas; Inne Crèvecoeur; Wannes D'Hertog; Pieter Baatsen; Matilde Masini; Mirjana Andjelkovic; Joris Van Loco; Christophe Matthys; Chantal Mathieu; Lut Overbergh; Bart Van der Schueren (PLoS ONE, 2014)
AIMS/HYPOTHESIS:To study the effects of cereulide, a food toxin often found at low concentrations in take-away meals, on beta-cell survival and function. METHODS:Cell death was quantified by Hoechst/Propidium Iodide in mouse (MIN6) and rat (INS-1E) beta-cell lines, whole mouse islets and control cell lines (HepG2 and COS-1). Beta-cell function was studied by glucose-stimulated insulin secretion (GSIS). Mechanisms of toxicity were evaluated in MIN6 cells by mRNA profiling, electron microscopy and mitochondrial function tests. RESULTS:24 h exposure to 5 ng/ml cereulide rendered almost all MIN6, INS-1E and pancreatic islets apoptotic, whereas cell death did not increase in the control cell lines. In MIN6 cells and murine islets, GSIS capacity was lost following 24 h exposure to 0.5 ng/ml cereulide (P<0.05). Cereulide exposure induced markers of mitochondrial stress including Puma (p53 up-regulated modulator of apoptosis, P<0.05) and general pro-apoptotic signals as Chop (CCAAT/-enhancer-binding protein homologous protein). Mitochondria appeared swollen upon transmission electron microscopy, basal respiration rate was reduced by 52% (P<0.05) and reactive oxygen species increased by more than twofold (P<0.05) following 24 h exposure to 0.25 and 0.50 ng/ml cereulide, respectively. CONCLUSIONS/INTERPRETATION:Cereulide causes apoptotic beta-cell death at low concentrations and impairs beta-cell function at even lower concentrations, with mitochondrial dysfunction underlying these defects. Thus, exposure to cereulide even at concentrations too low to cause systemic effects appears deleterious to the beta-cell.